Analysis of enzyme kinetic data - Cornish-Bowden, Athel (Oxford University Press, 1995)
This book introduces the theory and practice of statistical analysis of kinetic data for enzyme-catalysed reactions in the steady state. It includes a detailed description of a new program, Leonora, for analysing enzyme kinetic data, together with the program itself on an IBM PC compatible disk. Default options and a worked example are included for the novice but Analysis of Enzyme Kinetic Data provides readers with the necessary software and the required understanding to tailor an analysis to the requirements of their own research. Theoretical topics include basic principles of least-squares analysis; fitting the Michaelis-Menten equation by least-squares analysis; the general linear model; residual plots; maximum likelihood and efficiency; generalized medians; and robust regression. Practical topics include examination and fitting of statistical data; installation of Leonora, its use, simulations, menus, and customization.